ACTIVITIES IN CONSECUTIVE INTERPRETING TRAINING ONLINE AND OFFLINE - Merkulova, Svitlana (The Modern Higher Education Review, 2024)
The article is devoted to the study of peculiarities of basic practice activities in Consecutive Interpreting training online and offline. Consecutive Interpreting is defined as a practical discipline with pre-interpreting exercises that are implemented to train key elements of Consecutive Interpreting technique. Examination of different approaches to Consecutive Interpreting training and at the same time, combining interactive and individual exercises in the models of training online and offline, combination of both models in future practices allow transforming Consecutive Interpreting training to dynamic and busy process mastering professional interpreting competences to achieve goals in training market-driven interpreters. Studying current practices in training Consecutive Interpreting with pre-interpreting exercises that provide voice practices, training fluency, improving listening practices as well as achieve goals training glossary implementation in practice and create powerful fundamental experience in basic practice activities to achieve goals in professional training.